Scenario of mycobacterial and fungal infection in HIV seropositive patients and their co-relation with CD4 count in Western Uttar Pradesh - Pandey, Richa; Singh, Amit; Singh, Dharmendra Prasad; Verma, Rajesh Kumar; Kumar, Manoj; Kumar, Deepak (International Journal of Research in Medical Sciences, 2018)
Background: HIV infection is defined by sero-conversion and the detection of HIV-specific antibodies. Emergence and pandemic spread of acquired immunodeficiency syndrome is due to the exposure to human immunodeficiency virus (HIV). A decrease in CD4 count is at least partially responsible for the profound immunodeficiency that leads to various OIs in HIV- infected persons. When the CD4 count falls below 200cells/µL, there is irreversible breakdown of immune defence mechanism and patient become prey to a variety of human opportunistic pathogens.HIV positive patients must receive infections screening and access medical care before onset of advanced immunosuppression. Methods: In this study, total 230 HIV positive patients were selected during 18 months of study period. CD4 counts were estimated of all HIV positive cases. Positive HIV patients were investigated further to detect mycobacterial and fungal opportunistic infections. They were subjected to routine microscopy such as KOH mount, India ink, Gram’s staining for suspected fungal infection and ZN staining method for suspected mycobacterial infection. For fungal infection, samples were inoculated in two Sabouraud Dextrose Agar followed by different biochemical test and LPCB mount; for mycobacterial infection, samples were cultured on LJ medium followed by biochemical test. Results: In our study, maximum patients presented with complain of fever (90.43%), weight loss (73.91%) followed by loss of appetite (35.65%), breathlessness (33.91%), coughing (28.69%) and chest pain (22.17%). Overall prevalence of OIs (Mycobacterium and fungal) was 93 (40.43%) among 230 HIV positive patients. Among OIs 63(27.39%) patients were detected as having Mycobacterial infection and 41(17.82%) as had opportunistic fungal infections. Maximum OIs were related to patients with CD4 count 0-200 cells/µL followed by 201-400 Cells/µL. Most common OIs, among mycobacterial and opportunistic fungal infection were M. tuberculosis (50 isolates) and Candida spp. (26 isolates) respectively. Conclusions: This study provides important information about the risks of OIs at lower CD4 counts among HIV positive patients. These results highlight the need for early screening of HIV infected patients for opportunistic infections. There is also need to increase awareness in healthcare providers in order to improve decisions regarding prophylaxis for prevention of OIs and appropriate therapeutic intervention.